The mechanism of the Nfe2l2/Hmox1 signaling pathway in ferroptosis regulation in acute compartment syndrome. Issue 1 (4th October 2022) - Zheng, Tiejun; Huang, Zhao; Ling, He; Li, Junfeng; Cheng, Hong; Chen, Dingquan; Lu, Qinzhen; Zhao, Jinmin; Su, Wei
Abstract: Acute compartment syndrome (ACS) is a life‐threatening orthopedic emergency, which can even result in amputation. Ferroptosis is an iron‐dependent form of nonapoptotic cell death. This study investigated the mechanism of ferroptosis in ACS, explored candidate markers, and determined effective treatments. This study identified pathways involved in the development of ACS through gene set enrichment analysis (GSEA), Gene Ontology, Kyoto Encyclopedia of Genes and Genomes (KEGG), and GSEA of heme oxygenase 1 (Hmox1). Bioinformatics methods, combined with real‐time quantitative polymerase chain reaction, western blot analysis, and iron staining, were applied to determine whether ferroptosis was involved in the progression of ACS and to explore the mechanism of nuclear factor erythroid‐2‐related factor 2 (Nfe2l2)/Hmox1 in ferroptosis regulation. Optimal drugs for the treatment of ACS were also investigated using Connectivity Map. The ferroptosis pathway was enriched in GSEA, KEGG of DEGs, and GSEA of Hmox1. After ACS, the reactive oxygen species content, tissue iron content, and oxidative stress level increased, whereas glutathione peroxidase 4 protein expression decreased. The skeletal muscle was swollen and necrotized; the number of mitochondrial cristae became fewer or even disappeared, and Nfe2l2/Hmox1 expression increased at the transcriptional and protein levels. Hmox1 was highly expressed in ACS, indicating that Hmox1 is a possible marker for ACS. we could predict 12 potential target drugs for the treatment of ACS. In conclusion, Hmox1 was a potential candidate marker for ACS diagnosis. Ferroptosis was involved in the progression of ACS. It was speculated that ferroptosis is inhibited by the Nfe2l2/Hmox1 signaling pathway.